Learning Assessment for Madrasah Teacher: Strengthening Islamic Psychosocial and Emotional Intelligence - Desi Sukenti; Syahraini Tambak; Ermalinda Siregar (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research focused on developing the learning assessment teacher of Madrasah Aliyah by strengthening Islamic psychosocial and emotional intelligence, using ex post facto research design and involving 297 Madrasah Aliyah teachers in 12 regencies/cities Riau Province, Indonesia. A questionnaire was made to measure Islamic psychosocial and emotional intelligence and measure learning assessment madrasah teachers. The data were analyzed using inferential statistics. The research results show that the gender levels of the madrasah aliyah teachers influence Islamic psychosocial but do not affect emotional intelligence and learning assessment. It confirms that male and female teachers do not have different emotional intelligence and teacher learning assessment, but Islamic psychosocial effects are affected. Madrasah teachers' teaching experience affects Islamic psychosocial, emotional intelligence, and learning assessment of madrasah aliyah teachers. This research shows that Islamic psychosocial contribution is "strong" in developing teacher learning assessments, while emotional intelligence has a "strong enough" effect. This research concludes that the learning assessment of madrasah teachers can be maximally developed by simultaneously mastering Islamic psychosocial and emotional intelligence in madrasah. This research has implications for the theory of "developing learning assessment for madrasah teachers" in developing the professionalism of madrasah teachers.